2014
DOI: 10.1002/app.40387
|View full text |Cite
|
Sign up to set email alerts
|

Modification of jute fabric via laccase/t‐BHP‐mediated graft polymerization with acrylamide

Abstract: Enzymatic processes provide new perspectives for the modification of lignocellulose materials. Lignin is an excellent substrate for laccase, and the modification of lignin‐rich jute fabric via graft polymerization with acrylamide (AAm) mediated by laccase and tert‐butyl hydroperoxide (t‐BHP) was investigated in this study. The products obtained were characterized by Fourier transform infrared spectroscopy and scanning electron microscopy. The grafting rate was determined in terms of elemental analysis. The hyd… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 29 publications
0
3
0
Order By: Relevance
“…Apart from the common nucleophilic coupling of amines or the grafting of phenols, functionalisation with methacrylate or acrylamide is a popular strategy for the modification of lignocelluloses. Fan and co‐workers employed laccase‐initiated grafting using acrylamide and tert ‐butylhydroperoxide to functionalise jute fibres . Earlier studies confirmed that the presence of hydroperoxide was essential because the use of only laccase did not result in substantial grafting, but the necessity of laccase was dependent on the type of lignin .…”
Section: Laccase‐mediated Grafting On Lignocellulosesmentioning
confidence: 99%
“…Apart from the common nucleophilic coupling of amines or the grafting of phenols, functionalisation with methacrylate or acrylamide is a popular strategy for the modification of lignocelluloses. Fan and co‐workers employed laccase‐initiated grafting using acrylamide and tert ‐butylhydroperoxide to functionalise jute fibres . Earlier studies confirmed that the presence of hydroperoxide was essential because the use of only laccase did not result in substantial grafting, but the necessity of laccase was dependent on the type of lignin .…”
Section: Laccase‐mediated Grafting On Lignocellulosesmentioning
confidence: 99%
“…It can also be used for the functional modification of bast fiber by catalyzing the graft copolymerization of functional monomers onto the lignin of the fiber, which improves its hydrophilic, hydrophobic, anti-bacterial, and/or anti-oxidative properties, etc. (Silva et al 2011;Chen et al 2012;Dong et al 2014). Furthermore, laccase can also be used in the dyeing (Bai et al 2016;Jia et al 2017) and functional finishing (Montazer et al 2009;Hossain et al 2010;Fu et al 2015) of protein-based fibers during textile processing.…”
Section: Introductionmentioning
confidence: 99%
“…Also lignin represents an attractive target to graft polymers onto. Interestingly, this appears to be a laccase domain [61][62][63][64][65][66][67].…”
Section: Selected Examplesmentioning
confidence: 99%